Introduction - Prieto Hoces, Alejandro Ignacio (A+BE | Architecture and the Built Environment, 2018)
The thesis ‘COOLFACADE – Architectural integration of solar cooling strategies in the building envelope’ aims to shed light on the possibilities and constraints for architectural integration of solar cooling systems in façades, in order to support the design of climate responsive architectural products for office buildings as self-sufficient alternatives to conventional air-conditioning systems. This first chapter introduces the topics to be addressed throughout the dissertation, stating the main research problem, aim and focus of the study. Moreover, research questions are formulated, with consequent strategy and required methods to provide comprehensive answers to the defined challenges. Finally, the impact of the thesis is discussed in terms of its scientific and societal relevance, aiming to provide new knowledge to close research gaps in the field; but most importantly striving to promote further application of environmentally friendly technologies driven by renewable energy sources in the built environment.